Development of Principal Supervision Book to Improve the Quality of School Based Management Through Educational Literacy in Aceh Besar - Juwita Juwita; Akmaluddin Akmaluddin; Siti Mayang Sari (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to develop a principal supervision book to improve the quality of school-based management through educational literacy in Aceh Besar. This study is a research and development (Research & Development) Borg & Gall. Research & Development (R&D) is a research method carried out to produce a particular product, and test the effectiveness of the product. This development research uses the EDDIE method (Explore, Design, Development, Implementation, Evaluation), the phase of this study is seen from the development of the implementation process of the principal's role to the development of the learning process carried out by teachers. The results of the study prove that the results of the teacher's response were 82% with a very practical category, and the results of the principal's response were 88% with a very practical category, media validation was 96%, material/content validation was 98% and language validation was 94% so that the principal's supervision book was declared valid. Based on the evaluation results, it is proven that the use of the principal's supervision book is able to improve the quality of school-based management through educational literacy.